Motors for tram drives - Glinka, Tadeusz; Kulesz, Barbara; Jakubiec, Mieczysław (Transport, 2005)
This paper compares five different motor types used in variable speed drives: a dc motor with a mechanical commutator and with electromagnetic or permanent magnets excitation, a cage induction motor, asynchronous cascade with a slip‐ring motor and a brushless motor with PM excitation. These motors are to be used for tram drive and they should all be characterised by identical external dimensions and a cooling system. Rated power and efficiency are the principal comparison criteria.First Published Online: 27 Oct 2010